Economic policy and development in Nigeria, 1987 - Phillips, Adedotun O.; Ndekwu, Eddy Chika (Ibadan, Nigeria : Nigerian Institute of Social and Economic Research, 1988)
This book is an attempt to appraise policy performance and developments in the key sectors of the Nigerian economy during the year 1987. It is the second published output of the Nigerian Economy Watch (NEW) group which was created late in 1986 by the Nigerian Institute of Social and Economic Research (NISER), Ibadan to maintain regular surveillance on the Nigerian economy.
Includes bibliographical references.
II 17/01/2019
Loans
Keywords: Economic history; Economic policy; Nigeria